Are cumulus cells required during in vitro maturation of human oocytes at the germinal vesicle stage? a systematic review - Yurchuk, T; Petrushko, M; Piniaiev, V (39th Hybrid Annual Meeting of the ESHRE, Copenhagen – Denmark, 25-28 June 2023, 2023)
Accumulated data of more than 30 years of existence of IVM method can present to us how effective is the level of oocytes maturation in vitro obtained by aspiration follicles in vivo. Some studies reported that oocytes were matured after denudation, and in others they are cultured in cumulus oocyte complexes or in the presence of CC. Therefore, a comparison of oocyte maturation at the GV stage with and without CC was performed in this study.
Keywords: oocytes; cumulus cells